Ab interno trabecular bypass surgery with Schlemm´s canal microstent (Hydrus) for open angle glaucoma - Otarola, Francisco (Cochrane Database Syst Rev, 2020)
BACKGROUND: Glaucoma is a leading cause of irreversible blindness. A number of minimally‐invasive surgical techniques have been introduced as a treatment to prevent glaucoma from progressing; ab interno trabecular bypass surgery with the Schlemm's canal Hydrus microstent is one of them. OBJECTIVES: To evaluate the efficacy and safety of ab interno trabecular bypass surgery with the Hydrus microstent in treating people with open angle glaucoma (OAG). SEARCH METHODS: On 7 May 2019, we searched CENTRAL (2019, Issue 5), which contains the Cochrane Eyes and Vision Trials Register; Ovid MEDLINE; Ovid Embase; the ISRCTN registry; ClinicalTrials.gov; and the WHO ICTRP. SELECTION CRITERIA: We searched for randomised controlled trials (RCTs) of the Hydrus microstent, alone or with cataract surgery, compared to other surgical treatments (cataract surgery alone, other minimally‐invasive glaucoma device techniques, trabeculectomy), laser treatment, or medical treatment. DATA COLLECTION AND ANALYSIS: A minimum of three authors independently extracted data from reports of included studies, using a data collection form and analysed data, based on standard Cochrane methods. MAIN RESULTS: We included three published studies, with 808 people randomised. Two studies had multiple international recruitment centres in the USA and other countries. The third study had several sites based in Europe. All three studies were sponsored by the Hydrus manufacturer Ivantis Inc. All studies included participants with mainly mild or moderate OAG (mean deviation between ‐3.6 dB (decibel) and ‐8.4 dB in all study arms), which was controlled with medication in many participants (mean medicated intraocular pressure (IOP) 17.9 mmHg to 19.1 mmHg). There were no concerns regarding allocation concealment bias, but masking of outcome assessors was high or unclear risk in all studies; masking of participants was achieved, and losses to follow‐up were not a concern. Two studies compared the Hydrus microstent combined with cataract surgery to cataract surgery alone, in participants with visually significant cataracts and OAG. We found moderate‐certainty evidence that adding the Hydrus microstent to cataract surgery increased the proportion of participants who were medication‐free from about half to more than three quarters at 12‐month, short‐term follow‐up (risk ratio (RR) 1.59, 95% confidence interval (CI) 1.39 to 1.83; 2 studies, 639 participants; I² = 0%; and 24‐month, medium‐term follow‐up (RR 1.63, 95% CI 1.40 to 1.88; 2 studies, 619 participants; I² = 0%). The Hydrus microstent combined with cataract surgery reduced the medium‐term mean change in unmedicated IOP (after washout) by 2 mmHg more compared to cataract surgery alone (mean difference (MD) ‐2.00, 95% CI ‐2.69 to ‐1.31; 2 studies, 619 participants; I² = 0%; moderate‐certainty evidence), and the mean change in IOP‐lowering drops (MD ‐0.41, 95% CI ‐0.56 to ‐0.27; 2 studies, 619 participants; I² = 0%; low‐certainty evidence). We also found low‐certainty evidence that adding a Hydrus microstent to cataract surgery reduced the need for secondary glaucoma surgery from about 2.5% to less than 1% (RR 0.17, 95% CI 0.03 to 0.86; 2 studies, 653 participants; I² = 27%; low‐certainty evidence). Intraocular bleeding, loss of 2 or more visual acuity (VA) lines, and IOP spikes of 10 mmHg or more were rare in both groups; estimates were imprecise, and included both beneficial and harmful effects. There were no cases of endophthalmitis in either group. No data were available on the proportion of participants achieving IOP less than 21 mmHg, 17 mmHg, or 14 mmHg; health‐related quality of life (HRQOL), or visual field progression. One study provided short‐term data for the Hydrus microstent compared with the iStent trabecular micro‐bypass stent (iStent: implantation of two devices in a single procedure) in 152 participants with OAG (148 in analyses). Use of the Hydrus increased the proportion of medication‐free participants from about a quarter to about half compared to those who received iStent, but this estimate was imprecise (RR 1.94, 95% CI 1.21 to 3.11; low‐certainty evidence). Use of the Hydrus microstent reduced unmedicated IOP (after washout) by about 3 mmHg more than the iStent (MD ‐3.10, 95% CI ‐4.17 to ‐2.03; moderate‐certainty evidence), and the use of IOP‐lowering medication (MD ‐0.60, 95% CI ‐0.99 to ‐0.21; low‐certainty evidence). Both devices achieved a final IOP < 21 mmHg in most participants (Hydrus microstent: 91.8%; iStent: 84%; RR 1.09, 95% CI 0.97 to 1.23; low‐certainty evidence). None of the participants who received the Hydrus microstent (N = 74) required additional glaucoma surgery; two participants who received the iStent (N = 76) did. Few adverse events were found in either group. No data were available on the proportion of participants achieving IOP less than 17 mmHg or 14 mmHg, or on HRQOL. AUTHORS' CONCLUSIONS: In people with cataracts and generally mild to moderate OAG, there is moderate‐certainty evidence that the Hydrus microstent with cataract surgery compared to cataract surgery alone, likely increases the proportion of participants who do not require IOP lowering medication, and may further reduce IOP at short‐ and medium‐term follow‐up. There is moderate‐certainty evidence that the Hydrus microstent is probably more effective than the iStent in lowering IOP of people with OAG in the short‐term. Few studies were available on the effects of the Hydrus microstent, therefore the results of this review may not be applicable to all people with OAG, particularly in selected people with medically uncontrolled glaucoma, since IOP was controlled with medication in many participants in the included studies. Complications may be rare using the Hydrus microstent, as well as the comparator iStent, but larger studies are needed to investigate its safety.